Coordination of perishable product returns with imbalance information. (27th May 2009) - Yang, Jiaqin; Qin, Zhaoqiong; Lee, Huei
The speed of processing product returns is an important issue for a supply chain with perishable items. Especially, more manufacturers have recently started outsourcing the reverse logistics to third-party logistics (3-PL) providers. This paper proposes a model for such a supply chain with a single manufacturer and single 3-PL provider. The proposed model suggests a way of coordination between the manufacturer and its 3-PL provider with an optimal processing speed of product returns and allocation of total profits between the two parties. Specifically, the model provides the optimal coordination strategies for the manufacturer when both parties have the imbalance information about the processing cost of the 3-PL provider.